Vibroacoustic investigation of a batter head of a snare drum - E. B. Skrodzka; E. Hojan; R. Proksza (Archives of Acoustics, 2014)
The modal analysis of a batter head of a snare drum and measurements of the instrument's sound spectrum have been performed. The modal analysis results is comparable to the scarce literature reports. The analysis of the frequency maxima of the sound spectrum revealed significant discrepancies between the modal frequencies and those of the spectral peaks. It has been shown that the lowest mode (0, 1) is the strongest mode of radiation only for central excitation. For non-central excitation, the frequencies of spectral peaks differ significantly from the modal frequencies. It has been found that the batter head was not necessary the most strongly radiating element of the drum system and that the influence of other elements (the snare drum, the shell, the snares) are also very important as far as sound impression is concerned.